1987
DOI: 10.1007/bf00176472
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine gum: dose-related effects on cigarette smoking and subjective ratings

Abstract: The effects of nicotine-containing chewing gum on cigarette smoking and subjective and physiological response were evaluated in eight normal volunteers. Isolated subjects smoked their regular brand of cigarettes freely in a naturalistic laboratory environment while watching television or reading. Before 90-min smoking sessions subjects chewed two pieces of placebo or nicotine-containing gum (0, 2, 4, or 8 mg) under double-blind conditions. Each subject received each treatment four times in a mixed order across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…29 Compared to cigarette smoking, which delivers boli of nicotine to the brain within 10 seconds and achieves peak plasma concentrations after 5-10 minutes, 30 nicotine delivery via NRT is quite slow with peak plasma concentrations occurring after 20-30 minutes for gum 31 and 6-12 hours for various nicotine patches. 32 33 In any case, formal studies of abuse liability [34][35][36] have consistently shown that nicotine gum and patch have very low abuse liability. These forms of nicotine administration are simply not very reinforcing and, indeed, do not regularly maintain use even for as long as recommended by the instructions.…”
Section: Discussionmentioning
confidence: 99%
“…29 Compared to cigarette smoking, which delivers boli of nicotine to the brain within 10 seconds and achieves peak plasma concentrations after 5-10 minutes, 30 nicotine delivery via NRT is quite slow with peak plasma concentrations occurring after 20-30 minutes for gum 31 and 6-12 hours for various nicotine patches. 32 33 In any case, formal studies of abuse liability [34][35][36] have consistently shown that nicotine gum and patch have very low abuse liability. These forms of nicotine administration are simply not very reinforcing and, indeed, do not regularly maintain use even for as long as recommended by the instructions.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to the objective data on cigarette consumption following nicotine gum. reported by Nemeth-Coslett et al [1987], where higherdose gum led to some reductions in smoking behaviour.…”
Section: ]mentioning
confidence: 95%
“…Pickworth et al [1986] reported EEG changes indicative of increased alertness with 4 mg nicotine gum, but not with 2 mg gum. Nemeth-Coslett et al [1987] reported an increase in plasma nicotine following 4 mg gum, while levels following 2 mg gum were only slightly (non-significantly) higher than under the non-deprived placebo con dition. One major difficulty with research in this area is that 2 mg gum provides only a low dose of nicotine.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine gum also fails to produce euphoria (Snyder et al 1989). In fact, Nemeth-Coslett et al (1987) reported that 4 mg nicotine gum produced lower "euphoria" scores than placebo. Warburton (1988) presented data on the pleasure-stimulation and pleasure-relaxation effects of nicotine and other substances.…”
Section: Criterion 2: Psychoactivitymentioning
confidence: 97%